Syrian refugee and diaspora healthcare professionals: Case studies from the eastern mediterranean and European regions - Aula Abbara; Munzer Alkhalil; Kinan Wihba; Omer Abdrabbuh; Diana Rayes; Andrew Ghobrial; Manar Marzouk; Fadi Halabi; Mahmoud Hariri; Abdulkarim Ekzayez (Journal of Migration and Health)
Thousands of Syrian healthcare professionals have been forced to leave Syria since the onset of the uprisings in March 2011 and subsequent descent into conflict. Initially, many stayed in the eastern mediterranean region; however, as the conflict became increasingly protracted and employment policies for Healthcare Professionals (HCPs) became increasingly restrictive, some moved elsewhere, particularly to Germany and the United Kingdom, both of which have aimed to capitalise on both refugee and diaspora HCPs to support human resources gaps in their health systems. Our aim is to explore the different policy practices towards Syrian refugee and diaspora HCPs in the eastern mediterranean and European regions. Methods: We completed a narrative literature review and held a closed, virtual workshop in November 2022 in which 45 participants, most of whom had lived experience in the different refugee hosting contexts, participated. This allowed us to probe the primary themes arising from the literature review and the authors’ observations and present our findings as case studies. Results: We explore through case studies from countries near Syria (Turkey, Lebanon, Jordan, Egypt) and in Europe (Germany, UK) different policies which support or restrict entry into the health workforce. For host countries, those which implement policies that support retraining, accreditation and entry into the workforce have the potential for sustained and cost-effective benefit to their health systems; the impact of this on the HCPs and health system needs further exploration. Without such policies, Syrian HCPs are forced to work in the informal health sector such as in Lebanon or Egypt, leading to potential exploitation and security risks. Discussion: Now is an important opportunity to support Syrian and other refugee HCPs who have been forced to leave their homes to capitalise on their skills to explore the impacts of potentially effective policies and interventions. Such policies that aim to invest in refugee HCPs’ skills, further develop their aptitudes, and potentially establish a connection between them and their homeland in a mutually beneficial manner for both health systems in exile and in their homeland. Nonetheless, this topic still has large research gaps and remains in need of urgent research and data, particularly in view of the fall of the Syrian regime in December 2024 and its potential impacts.